Development and validation of an Ambulatory Care Patient Satisfaction Questionnaire to assess pharmacy services in Malaysia - Lai, Pauline Siew Mei; Chung, Wen Wei; Toh, Li Shean; Othman, Sajaratulnisah (Springer Verlag, 2018)
Background Assessing patient satisfaction regarding a pharmacy ambulatory care service is important as patient satisfaction is a determinant of the viability and sustainability of the service provided. Objective To develop and validate the Ambulatory Care Patient Satisfaction Questionnaire in Malaysia. Setting A public hospital in Malaysia with two outpatient pharmacies. The main outpatient pharmacy has an average waiting time of 1–2 h; whilst PharmCARE (which prepares repeat prescriptions in advance) has an average waiting time of 5–15 min. Method Our instrument was developed based on literature review, a theoretical framework and an expert panel. The initial version consisted of 20 Likert-type items (where a higher score indicates higher satisfaction) was administered to patients/carers who were ≥ 21 years, from November 2015 to June 2016 at baseline and 2 weeks later. Main outcome measure The psychometric properties of the instrument. Results A total of 200/220 participants agreed to participate (response rate = 90.9%): main outpatient pharmacy = 114, PharmCARE = 86. Flesch reading ease was 51.9. The final version consists of 17 items with five domains measuring information (4 items), accessibility (4 items), relationship (4 items), outcomes (2 items) and continuity of care (3 items). Participants who collected their medications from PharmCARE [78.0% (72.8–81.3)] were significantly more satisfied than participants from the main outpatient pharmacy [72.0% (68.0–76.0), p < 0.001]. The overall Cronbach’s alpha value was 0.839. Kappa values ranged from 0.681 to 0.914. Conclusion Our instrument was found to be a valid and reliable instrument to assess satisfaction of patients towards an ambulatory care pharmacy service in Malaysia.